1994
DOI: 10.1073/pnas.91.5.1810
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic, anaerobic bacteria isolated from a deepborehole in granite in Sweden.

Abstract: A borehole drilled to a total depth of 6779 m in granitic rock in Gravberg, Sweden, was sampled and examined for the presence ofanaerobic, thermophilic, fermenting bacteria and sulfate-reducing bacteria. Growth in enrichment cultures was obtained only from water samples collected from a specific sampling depth in the borehole (3500 m). The hole was cased down to a depth of 5278 m and open to the formation below that level. All the water below 2000 m in depth standing in the borehole at the time of sampling mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 23 publications
1
36
1
Order By: Relevance
“…To date, no formal characterization of fermentative bacteria isolated from such environments has been published, although short descriptions of strains SEBR 526ST and Gluc 1 have appeared previously (12,38). Our formal description of strain SEBR 526ST obtained from an oil field in this paper extends the physiological diversity and taxonomic diversity of thermophiles found in deep subsurface environments.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…To date, no formal characterization of fermentative bacteria isolated from such environments has been published, although short descriptions of strains SEBR 526ST and Gluc 1 have appeared previously (12,38). Our formal description of strain SEBR 526ST obtained from an oil field in this paper extends the physiological diversity and taxonomic diversity of thermophiles found in deep subsurface environments.…”
Section: Discussionmentioning
confidence: 68%
“…Additional sequence alignment and evolutionary distance analyses performed with members of this hylum indicated that the closest relatives of strain SEBR 5268 were T. Jinnii, T. brockii, and strain Gluc 1 ( Table 1). Isolation of strain Gluc 1 has been described, but detailed characteristics of this isolate have not been published yet (38). The 16s rRNA sequence of strain Gluc 1 was obtained from the Ribosomal Database Project (21).…”
Section: Enrichment and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Resulting, to some extent, from a decreasing availability of mineralizable organic carbon, microbial abundance, diversity, and activity in the vadose zone are lower than in surface soils but may increase again within the capillary fringe and the groundwater zone. (Holden and Fierer, 2005) Nevertheless, living microorganisms involved in the reduction of nitrate, sulfate and iron as well as acetogenesis, and methanogenesis have been reported from groundwater within granitic bedrock at depths of up to 978 m (Pedersen, 1997;Hallbeck and Pedersen, 2008) while the maximum depth of terrestrial subsurface drilling from which living organisms have been reported is 5.3 km (Szewzyk et al, 1994). Progress will require not just a cataloging of subsurface life, but an understanding of how the biodiversity of the subsurface transforms the mineralogy, shapes its physical and trophic environment, and influences the gases, water, solutes, and colloids moving through the CZ.…”
Section: Introductionmentioning
confidence: 99%
“…For a very long time, the mesophilic microbes that were recovered from the earth's crust were suspected to be surface contaminants. Increasing evidence of microbial populations thriving in deep geological formations has been given by recent key discoveries (39,51,53). Among these peculiar habitats, oil fields occurring at significant subsurface depth and, consequently, characterized by a high in situ temperature represent unique biotopes that constitute ecological niches providing suitable conditions to support thermophilic organisms (50).…”
mentioning
confidence: 99%